(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the prevalence of Traditional Chinese Medicine (TCM) syndromes and their association with TNM stages in lung cancer patients at Ho Chi Minh City Oncology Hospital. Methods: A cross-sectional study was conducted on 392 patients (Dec 2024 – May 2025). TNM stages and TCM syndromes were collected via direct interviews using a standardized questionnaire based on the 2023 CACM guidelines and expert consensus, and medical records. Data were analyzed using multivariate logistic regression, controlling for age, sex, BMI, and smoking history. Results: Qi deficiency (51.3%), Yin deficiency (35.5%), and Phlegm-dampness (27.0%). Multivariate analysis revealed no significant association between these three syndromes and TNM stages (p > 0.05). Notably, a history of smoking was identified as an independent risk factor, increasing the odds of Blood stasis by 1.84 times (aOR = 1.84, 95% CI: 1.04 – 3.31, p = 0.039). Conclusion: Qi deficiency, Yin deficiency, and Phlegm-dampness serve as foundational syndromes present throughout the disease process, independent of TNM staging. Smoking is a significant independent factor associated with Blood stasis.